2-Benzyliminomethyl-4-chlorophenol - Zhang, Xinli (International Union of Crystallography, 2008)
The title compound, C(14)H(12)ClNO, is a Schiff base derived from the condensation of equimolar quantities of 5-chlorosalicylaldehyde and 1-benzylamine. The molecule has a trans configuration with respect to the imine C=N double bond. The N atom is involved in an intramolecular O—H⋯N hydrogen bond.